The illustrated man eaudiobook - Bradbury, Ray (Recorded Books, 2018)
"Sometimes at night I can feel them, the pictures, like ants, crawling on my skin. Then I know they're doing what they have to do ... " Fantasy master Ray Bradbury weaves a narrative spanning from the depths of humankind's fears to the summit of their achievements in eighteen interconnected stories—visions of the future tattooed onto the body of an enigmatic traveler—in The Illustrated Man, one of the essential classics of speculative fiction from the author of The Martian Chronicles, Dandelion Wine, and The October Country.